INFLUENCE OF FIBER LENGTH AND MOISTURE CONTENT ON SOUND AND VIBRATION CHARACTERISTICS OF HEMP/EPOXY COMPOSITES - Singh, Raman; Nayak, Sandesh; Hegde, Sriharsha; NH, Padmaraj (Journal of Applied Engineering Science, 2023)
Bio-composites have become increasingly popular as a substitute for synthetic fibers over the last decade due to their eco-friendly nature. To utilize them effectively in engineering applications, particularly in the automotive industry, a thorough understanding of the material properties is necessary. This experimental investigation focuses on exploring the vibration-damping and acoustic properties of fiber composites made from hemp natural fiber and epoxy resin. The study involved the preparation of composite specimens using both short and long fibers through a hand layup process. The natural frequency and damping ratio of the specimen were computed from time-domain experimental data. The sound absorption coefficient of fiber specimens was determined in the frequency range of 63 Hz to 6300 Hz by using the impedance tube technique. The analysis revealed that the pre-treatment of fiber and the use of long fiber rather than short fiber enhances the damping properties of hemp fiber composites. Immersion of specimens in water resulted in the degradation of damping properties. Acoustic tests clearly showed that the ageing process affected short-treated fiber composites more significantly when compared to long-treated fiber composites.